Microstructure evolution and mechanical properties of copper bonding wire during continuous annealing. (May 2015) - Zhang, W.; Li, S. Y.; Yang, Z. X.; Mao, Y.; Xu, S. Y.
Abstract : In this study, the microstructure evolution and mechanical properties during continuous annealing for the copper bonding wire containing trace Mg and Ag were investigated. The relationship of microstructure evolution about recovery, recrystallisation and grain growth with breaking strength, hardness and elongation was analysed under different annealing temperatures for the studied copper wire with an area reduction of 99·95%. The results showed that the recovery occurred during annealing at 300–350°C, accompanying that breaking strength and hardness decreased, and elongation increased progressively. The recrystallisation happened during annealing at 350–460°C, and it accompanied that the breaking strength and hardness decreased, and elongation increased rapidly. The cold-drawn fibrous microstructure transformed into the recrystallised equiaxed grain. Annealing over 460°C caused the recrystallised grain growth and accompanying that breaking strength and hardness decreased, and elongation increased slowly. The proper combination of breaking strength and elongation was obtained by optimising continuous annealing during recrystallisation. Their results suggested that the high performance of copper bonding wire for semiconductor packaging can be developed by microstructure control through a proper continuous annealing.